Mutasi Induksi Dendrobium sylvanum var. flava Menggunakan Kolkisin secara In Vitro - Musalamah; Ni Made Armini Wiendi; Sri Rianawati (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2018)
ABSTRACTIn Vitro mutation using colchicine on 2 month of self-pollinated protocorm like bodies of Dendrobium sylvanum var. flava was conducted to determine the effects of concentration and immersion duration in colchicine on proliferation of PLBs, and to identify of ploidy variants based on stomatal variable. Research was arranged using factorial completely randomized design with three factors in three replications. The first factor was concentration of colchicine, consisted of five concentrations (0.02; 0.04, 0.06; 0.08; dan 0.1%). The second factor was duration of immersion in the colchicine, consisted of four durations (1; 24; 48; 72 hours). The third factor was proliferation medium consisted of two concentrations of BAP (1; 0.5 mg L-1). Analysis of variance showed the significant effect of colchicine treatment on percentage of survived explants. LD50 in media 1 mg L-1 BAP was obtained at a colchicine concentration of 0.069% with duration immersion of 58.19 hours. On Media 0.5 mg L-1 BAP, LD50 was obtained at colchicine concentration of 0.054% with duration immersion of 47.63 hours. Percentage of solid polyploid mutant of Dendrobium sylvanum var. flava can not be determined on MV2 generation because the stomata leaf showed chimeras based on the chloroplast number in cell guard and stomata size.Keywords: colchicines, Dendrobium sylvanum, mutation, number of chloroplast stomatal density.ABSTRAKMutasi dengan kolkisin pada PLBs hasil selfing Dendrobium sylvanum var. flava umur 2 bulan dilakukan secara In Vitro dengan tujuan mempelajari pengaruh konsentrasi kolkisin, durasi perendaman dalam kolkisin, media proliferasi terhadap pertumbuhan PLBs Dendrobium sylvanum var. flava serta mengidentifikasi variasi ploidi berdasarkan variabel stomata. Penelitian disusun dalam Rancangan Acak Lengkap Faktorial 3 Faktor dengan 3 ulangan. Faktor pertama ialah konsentrasi kolkisin yang terdiri atas 5 taraf (0.02; 0.04, 0.06; 0.08; dan 0.1%). Faktor kedua ialah durasi perendaman yang terdiri atas 4 taraf (1; 24; 48; 72 jam). Faktor ketiga ialah media proliferasi media V&W yang ditambah BAP terdiri atas 2 taraf (1; 0.5 mg L-1). Hasil analisis ragam menunjukkan pengaruh kolkisin yang nyata terhadap variabel persentase hidup. LD50 pada media 1 mg L-1 BAP diperoleh pada konsentrasi 0.069 % dengan durasi perendaman 58.19 jam. Pada media 0.5 mg L-1 BAP, LD50 diperoleh pada konsentrasi 0.054 % dengan durasi perendaman 47.63 jam. Persentase mutan poliploid pada MV2 Dendrobium sylvanum var. flava ini belum dapat ditentukan karena stomata daunnya masih kimera berdasarkan karakter jumlah kloroplas sel penjaga dan ukuran stomata.Kata kunci: Dendrobium sylvanum, jumlah kloroplas, kerapatan stomata, kolkisin, mutasi.